Trans-hiatal oesophagectomy in a AIDS patient - M I M de Zoysa; S Sivaganesh; A U Abayadeera; K Buddakorala (Southern African Journal of HIV Medicine, 2011)
A 49-year-old man was diagnosed as HIV infected, with a CD4 count of 60 cells/µl. He was started on an antiretroviral treatment regimen comprising zidovudine, lamivudine and efavirenz. Following treatment, his CD4 count improved and the viral load was undetectable. He was subsequently found to have a moderately differentiated adenocarcinoma of the lower oesophagus.